Tratamento multidisciplinar: relato de casos clínicos - Boeck, Eloisa Marcantonio; Margonar, Rogério; Boeck Neto, Rodolfo Jorge; Lunardi, Nadia; Marcantonio Júnior, Elcio [UNESP] (My University, 2014)
Introduction: Adult patients are more prone to periodontal disease mainly caused by poor plaque control. In these patients, orthodontic movement is not contraindicated, but it is necessary to evaluate their periodontal status so that we can establish the appropriate treatment plan. Objective: The objective of this article is to describe and discuss the clinical cases of severely periodontally compromised individuals in need of oral rehabilitation. Methods: The study consisted of orthodontic treatment of two cases with periodontal involvement. After clinical and radiographic examinations, the cases were analyzed by a multidisciplinary team of Orthodontics, Periodontics and Prosthodontics, in order to provide the patient with the best possible esthetic, functional and stability outcomes. Periodontal treatment consisted of supra and subgingival scaling prior to orthodontic treatment, and regular maintenance performed on a quarterly basis throughout orthodontic movement. Activation was carried out every 45 to 50 days, with light forces. Retention remains to the present day, even after completion of the rehabilitation. Conclusion: Multidisciplinary oral rehabilitation treatment yields satisfactory results. The interaction between Orthodontics and Periodontics reveals that patients with reduced, but healthy periodontium, can receive orthodontic treatment as long as the forces applied do not exceed patient's biological limits.

Introdução: O paciente adulto apresenta maior predisposição para doença periodontal, decorrente, principalmente, do mal controle de placa. Nesses pacientes, a movimentação ortodôntica não é contraindicada, porém, é necessária uma avaliação da condição periodontal para que se possa estabelecer o plano de tratamento apropriado. Objetivo: Descrever e discutir casos clínicos de indivíduos com necessidade de reabilitação bucal e com periodonto severamente comprometido. Métodos: Os métodos consistiram no tratamento ortodôntico de dois casos com comprometimento periodontal. Após exames clínicos e radiográficos, os casos foram analisados de forma multidisciplinar, envolvendo as especialidades de Ortodontia, Periodontia e Prótese, com objetivo de proporcionar ao paciente os melhores resultados estético, funcional e estabilidade. O tratamento periodontal consistiu de raspagem supra- e subgengival, previamente ao tratamento ortodôntico, e programa de manutenção periódica trimestral durante toda movimentação ortodôntica. As ativações foram realizadas em intervalos de 45 a 50 dias, com a utilização de forças leves, sendo utilizadas contenções em ambas as arcadas, mesmo após a finalização da reabilitação. Conclusão: O tratamento reabilitador bucal, quando feito de forma multidisciplinar, traz resultados bastante satisfatórios. A interação da Ortodontia e da Periodontia comprovou que pacientes com periodonto reduzido, porém saudável, podem receber tratamento ortodôntico, desde que as forças não excedam o limite biológico desse.
Keywords: Orthodontics; Periodontics; Oral rehabilitation; Ortodontia corretiva; Periodontia; Reabilitação bucal